PENGETAHUAN ORANG TUA TENTANG KECACINGAN DAN PENGOBATAN TERHADAP KEJADIAN INFEKSI SOIL TRANSMITTED HELMINTH DI SDN CIBEREM KECAMATAN SUMBANG KABUPATEN BANYUMAS: A CROSS SECTIONAL STUDY - Lieza Dwianasari Susiawan; Wahyudin Wahyudin; Octavia Permata Sari; Wisnu Budi Pramono; Fiona Annisa Bahiyah (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Soil Transmitted Helminths (STH) infection is a disease caused by nematodes and often occurs among elementary school age children. One factor that can influence the occurrence of recurrent infections is parents' lack of understanding about worm treatment. Errors in treating worms can be influenced by several factors, one of which is the level of parental knowledge. To determine the relationship between the level of parental knowledge about worms and treatment on the incidence of Soil Transmitted Helminth infections at SDN Ciberem, Sumbang District, Banyumas Regency. Analytical research is an observational study with a cross-sectional design on 96 Ciberem Elementary School students using purposive sampling techniques. Data collection was carried out by questionnaires on parental knowledge and fecal examination at the FK Unsoed Parasitology Laboratory using the floating method (qualitative). Hypothesis analysis uses Fisher's Exact test. Result: The prevalence of STH infection at SDN Ciberem was 5.2% with the worm type Trichuris trichiura. The results of the Fisher's Exact statistical test showed that parental knowledge about worms (p= 0.052) did not have a significant relationship with the incidence of STH infection. The level of parental knowledge about worm treatment (p=0.033) has a significant relationship with the incidence of STH infection. Conclusion: There was no relationship between the level of parental knowledge about worms and the incidence of STH infection. There is a relationship between the level of parental knowledge about worm treatment and the incidence of STH infection.